2022
DOI: 10.1016/j.jbc.2021.101470
|View full text |Cite
|
Sign up to set email alerts
|

Update and nomenclature proposal for mammalian lysophospholipid acyltransferases, which create membrane phospholipid diversity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 196 publications
2
52
0
Order By: Relevance
“…During apoptosis, PSs are transferred to the outer layer and act as labels for the cells, which undergo phagocytosis [ 46 ]. Moreover, since the membrane’s fluidity and ability to adapt to dynamic changes is associated with changes in lipid composition, changes in membrane composition may be an indicator of ongoing carcinogenesis [ 47 ]. It has previously been reported that, apart from changes in the phospholipid content, neoplasms also exhibit alterations in their sphingolipid content [ 42 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…During apoptosis, PSs are transferred to the outer layer and act as labels for the cells, which undergo phagocytosis [ 46 ]. Moreover, since the membrane’s fluidity and ability to adapt to dynamic changes is associated with changes in lipid composition, changes in membrane composition may be an indicator of ongoing carcinogenesis [ 47 ]. It has previously been reported that, apart from changes in the phospholipid content, neoplasms also exhibit alterations in their sphingolipid content [ 42 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes that were called lysophospholipid acyltransferases (LPLATs) were suggested to be organised into two main families of proteins, then termed lysophosphatidic acid acyltransferases (LPAATs) and membrane bound O-acyltransferases (MBOATs) [34][35][36][37][38][39][40][41][42][43][44][45][46]. For readers interested in a comprehensive recent review of the area including full descriptions of studies that characterised cloned proteins in vitro please see [47]. However, the naming conventions that were used to refer to LPLATs over the decades created significant confusion in the field.…”
Section: Elucidating the Enzymes Involved Using Molecular Biology App...mentioning
confidence: 99%
“…LPLAT8 and 9 are considered monotopic membrane proteins, with LPLAT8-10 predicted to be anchored via N-terminal helices. These LPLATs are widely expressed in mammalian tissues, and are mainly localised to the ER membrane, although some are also found on Golgi, mitochondrial, nuclear membrane or lipid droplets [47]. As examples of AGPAT family members, the first cloned enzyme shown to generate PC-containing 20:4 was LPLAT9 (LPCAT2) while a reduction in PC-20:4 was shown to occur in LPLAT12 mice [48][49][50].…”
Section: Agpat Familymentioning
confidence: 99%
See 2 more Smart Citations